Teatralitet og performativitet: to sider af samme sag – næsten? - Kjølner, Torunn (Peripeti, 2021)
This article presents an overview of different bodies of research in the field of theatre science. Asking who does what with the concepts of performativity and theatricality it demonstrates how internal scientific battles as to the legitimization of theatre science or as to the preferred types of theatre are fought. It is argued that both concepts should be available for the pragmatic discussion of how theatre makes its effects, avoiding the traps of essentialism. The theatrical theatre will highlight the effects that can be rehearsed and used in front of the audience. A theatre oriented towards the performative will insist on the creativity of the moment, the presence to be captured.